PENGEMBANGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERINTEGRASI DENGAN MEDIA QUIZIZZ UNTUK MENINGKATKAN MINAT BELAJAR DAN KETERAMPILAN BERPIKIR KRITIS SISWA - Undariyantiningsih, doris; Cintamulya, Imas; Christina Innocenti Tumiar P (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Developing critical thinking considered as an important goal of education. Critical thinking skills could help students to overcome the problems faced by students. This research aimed at developing a problem-based learning model integrated with Quizizz media to improve students' learning interest and critical thinking skills. This study applied the Research & Development (R&D) technique and the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The resulting product is a problem-based learning model design integrated with Quizizz, a teaching module, and Quizizz media. The design was validated by validators. The validation results of the development that related to content are assessed from nine aspects having an average value of 88.84%, with the category very valid or used without improvement. The validation results in terms of model constructs have an average value of 87.21% with the criteria very valid or used without improvement. The practicality test of the learning model was carried out by implementation observations, it had average value of 93.75% with the category of very practical or used without improvement. The Effectiveness Test using the Mann-Whitney test obtained an Asymp Sig (2-tailed) value of 0.020<0.05 and U count 8<U table 10. It showed that there was significance difference between the increase in students' critical thinking abilities with impulsive and reflective cognitive styles. The results of the survey showed that the responses of students with an impulsive cognitive style to learning model activities were 84.67% and the responses of students with a reflective cognitive style were 91.49%. it can be concluded that the problem-based learning model integrated with Quizizz media can improve students' learning interest and critical thinking skills.